A simple approach for CTAB-free and biofunctionalized gold nanorods to construct photothermal active nanomedicine for potential in vivo applications in cancer cells and scar treatment - Foti, Alice; Clépoint, Benjamin; Fraix, Aurore; D’Urso, Luisa; De Bonis, Angela; Satriano, Cristina (Frontiers in Materials, 2024)
Cetyltrimethylammonium bromide (CTAB), a surfactant commonly used in the synthesis of gold nanorods (AuNR), presents challenges owing to cytotoxicity in biological applications, limiting their biomedical applicability, particularly in cancer therapy. This study introduces a straightforward methodology for the effective removal of CTAB by utilizing a combination of ligand replacement and surface bioconjugation processes that efficiently eliminates CTAB and simultaneously functionalizes nanorods with hyaluronic acid (HA) to enhance biocompatibility and introduce targeting capabilities toward cancer cells. The surface chemistry modification of CTAB-capped and CTAB-free AuNR, before and after the functionalization with HA, was scrutinized by UV–visible, surface-enhanced Raman scattering (SERS), attenuated total reflectance (ATR) Fourier-transform infrared (FTIR), and X-ray photoelectron (XPS) spectroscopies. The surface charge, size, and morphology of the different plasmonic nanoparticles were characterized by zeta potential, dynamic light scattering (DLS), and transmission electron microscopy (TEM). The photothermal response was assessed by laser irradiation and thermal camera measurements. Proof-of-work in vitro cellular experiments of cytotoxicity and oxidative stress were carried out on prostate cancer cells, PC-3, overexpressing the CD44 cell surface receptor specifically recognized by HA, in comparison with the CD44-negative murine fibroblasts (3T3 cell line) by MTT and MitoSOX assays, respectively. Cellular uptake and organelle alteration were scrutinized by confocal laser scanning microscopy (LSM), while the perturbative effects on cell migration were studied by optical microscopy (wound scratch assay). The study’s findings offer a promising pathway to tune the gold nanorod properties in cancer treatment by reducing cytotoxicity and enhancing targeted therapeutic efficacy, as well as in the control of scar tissue formation.